Reduced repair of the oxidative 8-oxoguanine DNA damage and risk of head and neck cancer - Paz-Elizur, Tamar; Ben-Yosef, Rami; Elinger, Dalia; Vexler, Akiva; Krupsky, Meir; Berrebi, Alain; Shani, Adi; Schechtman, Edna; Freedman, Laurence; Livneh, Zvi (Cancer research (Chicago, Ill.), 2006)
An increasing number of studies indicate that reduced DNA-repair capacity is associated with increased cancer risk. Using a functional assay for the removal of the oxidative DNA lesion 8-oxoguanine by the DNA-repair enzyme 8-oxoguanine DNA glycosylase 1 (OGG1), we have previously shown that reduced OGG activity is a risk factor in lung cancer. Here, we report that OGG activity in peripheral blood mononuclear cells from 37 cases with squamous cell carcinoma of the head and neck (SCCHN) was significantly lower than in 93 control subjects, frequency matched for age and gender. Retesting of OGG activity 3 to 4 years after diagnosis and successful treatment of 18 individuals who recovered from the disease showed that OGG activity values were similar to those determined at diagnosis, suggesting that reduced OGG activity in case patients was not caused by the disease. Logistic regression analysis indicated that the adjusted odds ratio (OR) associated with a unit decrease in OGG activity was statistically significantly increased [OR, 2.3; 95% confidence interval (95% CI), 1.5-3.4]. Individuals in the lowest tertile of OGG activity exhibited an increased risk of SCCHN with an OR of 7.0 (95% CI, 2.0-24.5). The combination of smoking and low OGG was associated with a highly increased estimated relative risk for SCCHN. These results suggest that low OGG is associated with the risk of SCCHN, and if confirmed by additional epidemiologic studies, screening of smokers for low OGG activity might be used as a strategy for the prevention of lung cancer and SCCHN.